Planning Management To Improve The Value Of The Lightning Protection Grounding System At The Ccr Building At Sultan Syarif Kasim II International Airport Pekanbaru - Muhammad Caesar Akbar; Tri Dina Agustina Panjaitan (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Sultan Syarif Kasim II International Airport Pekanbaru is equipped with an Airfield Lighting System (ALS) just like airports in general. ALS is a visual landing aid that functions to assist and serve aircraft during takeoff, landing and taxiing so that they can move efficiently and safely. The ALS is supplied by CCR (Constant Current Regulator). CCR is a constant current power supply used to supply ALS equipment. The CCR building at Sultan Syarif Kasim II International Airport Pekanbaru is also equipped with a lightning rod with an electrostatic type which is intended to be able to flow lightning currents directly to the ground and not hit the building and not damage the electronic equipment in the CCR building. But in November there was a damage to the CCR module of the PAPI lamp so that the CCR could not operate. This is due to a strong lightning strike that results in a "Local Bus Down Error" on the CCR of the PAPI lamp. The factor that affected the occurrence of the event was the poor quality of the lightning rod grounding system in the building where the value of the lightning rod grounding system was 5.7Ω, the value had exceeded the 2011 PUIL rules where the value of a good grounding system was <5Ω, so improvements were needed to the value of the lightning rod grounding system in the building in accordance with the 2011 PUIL rules.